PRESENTATION OF BULLYING CASES AMONG ELEMENTARY STUDENTS: PSYCHOLOGICAL ANALYSIS AND CORRECTION APPROACHES - Berdiyeva Gulmira Juraevna; Ibragimova Shahzoda Zavqiddin qizi (The Conference Hub, 2025)
This article examines the manifestation of bullying among primary school students, with a psychological analysis and correctional approaches aimed at prevention and support. The study investigates both overt and covert forms of aggression, their connection with personal traits, family background, and classroom social dynamics. It also outlines effective psychocorrectional methods tailored to the emotional-intellectual development of children.
Keywords: bullying, psychological analysis, primary school, correctional methods, social-emotional development.